SISTEM PENDUKUNG KEPUTUSAN PENANGANAN PENYAKIT DENGUE HEMORRHAGIC FEVER (DBD) DENGAN MOTEDE SAW - Sijabat, Maruba; Hara Pardede, Akim Manaor; Prahmana, I Gusti (Journal of Mathematics and Technology (MATECH), 2023)
Dengue hemorrhagic Fever/Dengue Hemorrhagic Fever is an acute febrile disease that can cause death and is caused by four serotypes of viruses of the genus Flavivirus, RNA viruses of the Flaviviridae family. Dengue is transmitted to humans mainly by the Aedes aegypti mosquito and the Aedes albopictus mosquito, and is also transmitted by Aedes polynesiensis and several other mosquito species that actively suck blood during the day. After the infective blood is inhaled by the mosquito, the virus enters the mosquito's salivary glands and multiplies to become infective within 8-10 days, which is called the extrinsic incubation period. Dengue cases (dengue hemorrhagic fever) continue to increase every year, according to the World Health Organization (WHO) as much as 3.21% in 2020 of the total world population. In Indonesia, cases reached 16,320, in June 2021, which is still a high number. The number of cases in April was 6,417 cases, this prevalence increased when compared to cases in May 2021 which were 9,903 cases. Due to DHF (Dengue hemorrhagic fever) which increased causing the death rate in May of 98 cases, an increase in June was recorded 147 cases. Therefore, it is necessary to take decisions that can be used to support and assist management in making semi-structured and unstructured decisions. To determine the treatment mitgasi action on dengue hemorrhagic fever quickly and reduce the high risk of contracting dengue fever. Problems in dengue hemorrhagic fever can be solved by using the saw method to determine the handling action quickly. From the tests conducted obtained values ranging from the lowest value to the lowest in the case of dengue hemorrhagic fever (DHF), so based on the acquisition of the highest value of 0.7525 (75.25%) in Alternative 1.